2021
DOI: 10.3389/fonc.2021.705948
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Discovery a Novel SARS-CoV-2 Variant in a Six-Months Long-Term Swab Positive Female Suffering From Non-Hodgkin Lymphoma

Abstract: BackgroundWe report the case of a woman with non-Hodgkin lymphoma who remained positive on the molecular assay for SARS-CoV-2 for six months: she has never experienced a severe form of COVID-19 although in absence of seroconversion.MethodsThe whole SARS-CoV-2 genome analysis was performed by the CleanPlex SARS-CoV-2 Research and Surveillance NGS Panel (PARAGON GENOMICS, Hayward, USA).ResultsWe found twenty-two mutations in SARS-CoV-2 genome and a novel deleterious ORF3a frameshift c.766_769del corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…29 Patients with hematological malignancies such as lymphoma appear to have a greater risk of contracting SARS-CoV-2 infection, as well as experiencing more severe and prolonged infection. 30 Due to the nature of lymphoma, or B-cell targeting treatments, lymphopenia or immunosuppression, are often seen. A study by Yasuda et al, found that patients who underwent recent rituximab therapy were less likely to develop anti-SARS-CoV-2 antibodies thereby, becoming more likely to experience severe and prolonged COVID-19 infections, as well as bacterial or fungal pneumonia.…”
Section: Literature Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…29 Patients with hematological malignancies such as lymphoma appear to have a greater risk of contracting SARS-CoV-2 infection, as well as experiencing more severe and prolonged infection. 30 Due to the nature of lymphoma, or B-cell targeting treatments, lymphopenia or immunosuppression, are often seen. A study by Yasuda et al, found that patients who underwent recent rituximab therapy were less likely to develop anti-SARS-CoV-2 antibodies thereby, becoming more likely to experience severe and prolonged COVID-19 infections, as well as bacterial or fungal pneumonia.…”
Section: Literature Review Methodologymentioning
confidence: 99%
“…Patients with hematological malignancies such as lymphoma appear to have a greater risk of contracting SARS‐CoV‐2 infection, as well as experiencing more severe and prolonged infection 30 . Due to the nature of lymphoma, or B‐cell targeting treatments, lymphopenia or immunosuppression, are often seen.…”
Section: Pathophysiological Effects Of Covid‐19 In Lymphoma Patientsmentioning
confidence: 99%
“…As described in the "Direct Acting Antivirals" section, Brown et al suggested that combination of RDV and passive humoral therapy is superior to RDV alone for clearing protracted infections [41•]; however, Hueso et al used CCP alone with success [46•]. Smaller case series and case reports have shown clinical improvement and/or viral clearance [48][49][50][51][52][53], while others have failed to show effectiveness [2,6].…”
Section: Convalescent Plasmamentioning
confidence: 99%